Genetic diversity of Dipterocarpus dyeri in the tropical forests of Tan Phu (Dong Nai) - Hai Ha, Nguyen Thi; Duc, Nguyen Minh; Hien, Dang Phan; Duy, Vu Dinh; Don, Pham Quy; Tuan Anh, Nguyen Le; The, Truong Huu; Tam, Nguyen Minh (Academia Journal of Biology, 2016)
Dipterocarpus dyeri (Dipterocarpaceae) is widely distributed in lowland rainforests in southern Vietnam. Due to overexploitation and habitat destruction in the 1980s and 1990s, the species is listed as a threatened species. To conserve the species in tropical forests, genetic diversity was investigated on the basis of eight microsatellite (single sequence repeat, SSR). In all, sixty D. dyeri individuals in Tan Phu rainforests were analyzed in this study. All the eight loci were polymorphic. A total of 30 alelles were observed across the studied loci. The polymorphic information content (PIC) averaged 0,459 (0,113-0,727) and indicated low polymorphic value. Other values including discrimination power (PD = 0,619), resolving power (Rp = 2,653) and Marker index (MI = 1,190) were revealed. The SSR data indicated a high genetic diversity (A = 3.7; Ho = 0.375 and He = 0.427) and the inbreeding value was high, Fis = 0.064. The dendrogram grouping the individuals by unweighted pair-group method with arithmetic averages method revealed different clusters. The most individuals in a cluster were related with closed geographic diatances. This study also indicated the importance of conserving the genetic resources of Dipterocarpus dyeri species in Tan Phu rainforests.